When the moon hits your eye [large type] - Scalzi, John, 1969- (Thorndike Press large print high octane., 2025)
"When the Moon inexplicably turns to cheese, humanity grapples with the absurd transformation through the perspectives of astronauts, billionaires, professors, and everyday people, confronting faith, science and survival over a single surreal lunar cycle." --